Deteriorating Bonds of Relationships: A few Concerns: Exploring the Impact of Changing Indian Society on Interpersonal Relationships (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The present study was aimed at investigating the causes of deteriorating bonds of relationshipsin Indian society and its impact on the life of the individual and society at large. The main factors found tobe important were the family experiences of childhood, especially the attachment patterns, therelationship of child with parents and with other family members, change in family structure from jointto nuclear,the changed status of women from home makers to working and bearing the dualresponsibility of both home and professional life, erosion of ancient Indian cultural values due toglobalisation, the effect of media, were a few factors which emerged to be related with degradation inhuman relations. The socialization process and the caring relationship among the family membersstemmed out to be the most important factors as the solution to the problem.